2015
DOI: 10.1177/1039856215609762
|View full text |Cite
|
Sign up to set email alerts
|

#IHMayDay: tweeting for empowerment and social and emotional wellbeing

Abstract: Twitter-based events such as #IHMayDay and initiatives such as the rotated, curated account @IndigenousX are powerful platforms for learning, exchange, advocacy and dialogue about the social and emotional wellbeing and mental health of Aboriginal and Torres Strait Islander peoples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 6 publications
2
30
0
Order By: Relevance
“…While only 5 studies were found, a narrative summary of these studies was deemed appropriate to assist in understanding the role of social media in improving the health of Aboriginal Australians and guide future research in this area. Of the 5 included papers, 3 used qualitative approaches [11,20,21] and 2 used multiple methods [22,23]. Based on the quality assessment tool used, from the 5 studies, 2 were of neutral quality, 2 were of poor quality, and 1 was of good quality (Multimedia Appendix 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While only 5 studies were found, a narrative summary of these studies was deemed appropriate to assist in understanding the role of social media in improving the health of Aboriginal Australians and guide future research in this area. Of the 5 included papers, 3 used qualitative approaches [11,20,21] and 2 used multiple methods [22,23]. Based on the quality assessment tool used, from the 5 studies, 2 were of neutral quality, 2 were of poor quality, and 1 was of good quality (Multimedia Appendix 1).…”
Section: Resultsmentioning
confidence: 99%
“…One study found that age was associated with social media use for health [21]. Older Aboriginal groups often found using social media for health more complex and, in some cases, having detrimental health outcomes [21], whereas younger groups were more readily receptive to using social media for their health and well-being [11,20,21]. All studies mentioned the need for more time for participants to become familiar with utilizing social media for it to have an impact on health; the reason acknowledged was the relative infancy of social media use and Aboriginal health within Australia [21,23].…”
Section: Resultsmentioning
confidence: 99%
“…Mr Pearson has been involved in all these events, which have also been supported by the @IndigenousX and @WePublicHealth accounts. A subsequent analysis of a selection of tweets from the 2014 event found that SEWB was a dominant theme (Sweet et al, ).…”
Section: Narrativesmentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander people, health professionals, and health organisations are harnessing Twitter in diverse and innovative ways that are enhancing social and emotional wellbeing (SEWB) and self‐determination (Sweet, Geia, Dudgeon, & McCallum, ; Waller et al, ). One such example is the rotated curated account @IndigenousX, which can be variously understood as a work of social innovation and entrepreneurship, a form of community development and advocacy, and an example of community‐generated journalism (Sweet, Pearson, & Dudgeon, ).…”
Section: Introductionmentioning
confidence: 99%
“…It can also be based on large scale quantitative analysis of trends or topics—from how a political idea spreads, how earthquakes are experienced, or how sentiments expressed on Twitter correlate to market performance or to geography [ 15 ]. Researchers have also taken advantage of the way Twitter users group tweets under particular hashtags, looking at how #iranelection connected protesters and international supporters after Iran’s 2009 elections [ 16 ], how #whyistayed transformed online personal expressions of experience of domestic violence to collective political action [ 17 ], and how #IHMayDay assisted dialogue, advocacy and exchange about the social and emotional wellbeing of Aboriginal and Torres Strait Islander peoples [ 18 ].…”
Section: Introductionmentioning
confidence: 99%